Integration Between Cerebral Hemispheres Contributes to Defense Mechanisms - Paradiso, Sergio; Brown, Warren S.; Porcerelli, John H.; Tranel, Daniel; Adolphs, Ralph; Paul, Lynn K. (Frontiers in Psychology, 2020)
Defense mechanisms are mental functions which facilitate coping when real or imagined events challenge personal wishes, needs, and feelings. Whether defense mechanisms have a specific neural basis is unknown. The present research tested the hypothesis that interhemispheric integration plays a critical role in defense mechanism development, by studying a unique sample of patients born without the corpus callosum (agenesis of the corpus callosum; AgCC). Adults with AgCC (N=27) and matched healthy volunteers (N=30) were compared on defense mechanism use across increasing levels of developmental maturity (denial, least; projection, intermediate; identification, most). Narratives generated in response to Thematic Apperception Test images were scored according to the Defense Mechanism Manual. Greater use of denial and less identification was found in persons with AgCC, compared to healthy comparisons. This difference emerged after age 18 when full maturation of defenses among healthy individuals was expected. The findings provide clinically important characterization of social and emotional processing in persons with AgCC. More broadly, the results support the hypothesis that functional integration across the hemispheres is important for the development of defense mechanisms.